KAJIAN ATAS TATAKELOLA TEKNOLOGI INFORMASI: PENGERTIAN, PANDUAN.PANDUAN, SERTA CONTOH PENERAPAN - Michael Iskandar (Center for Economic Studies Universitas Katolik Parahyangan, 2008)
Governance of the firm's information technology (tr Governance) has become more and more important to the succesiiut management of corporations around the world. To hchieve tr Governaice, each corporation may de.velo.p its own unique approach, or otherwise it may utilize a number of guidelines that have been developed, such as the s.arbanes-oxley Act (sox), committee of sponsoring organizations of the Treadway commission Framework (coso), and-conrol objectives for lnformation Technology (coBtr). This paper dr.scusies tr Governance as a concept, explains some of the guidelines mentioned above that can be used to achieve it, attempts a categorization of those guidelines, and ends with an example. tn this example the framework used is coBlr and the lr governance aspect evaluated is the business continuity plan.",